2017
DOI: 10.1007/s10902-017-9901-y
|View full text |Cite
|
Sign up to set email alerts
|

Mindful and Resilient? Incremental Validity of Sense of Coherence Over Mindfulness and Big Five Personality Factors for Quality of Life Outcomes

Abstract: Nutzungsbedingungen: Dieser Text wird unter einer Deposit-Lizenz (Keine Weiterverbreitung-keine Bearbeitung) zur Verfügung gestellt. Gewährt wird ein nicht exklusives, nicht übertragbares, persönliches und beschränktes Recht auf Nutzung dieses Dokuments. Dieses Dokument ist ausschließlich für den persönlichen, nicht-kommerziellen Gebrauch bestimmt. Auf sämtlichen Kopien dieses Dokuments müssen alle Urheberrechtshinweise und sonstigen Hinweise auf gesetzlichen Schutz beibehalten werden. Sie dürfen dieses Dokume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 77 publications
(100 reference statements)
3
19
0
1
Order By: Relevance
“…The observed association is also noteworthy given that school connectedness was one of the strongest predictors of depression (Renshaw 2018). Our suggest that a school connectedness may serve as an intermediate link between neuroticism and depression of college students (Grevenstein, Aguilar-Raab, & Bluemke, 2018;Weissman, Prusoff, & Klerman, 1978).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The observed association is also noteworthy given that school connectedness was one of the strongest predictors of depression (Renshaw 2018). Our suggest that a school connectedness may serve as an intermediate link between neuroticism and depression of college students (Grevenstein, Aguilar-Raab, & Bluemke, 2018;Weissman, Prusoff, & Klerman, 1978).…”
Section: Discussionmentioning
confidence: 53%
“…Individual difference characteristics outside of the traditional Big Five such as resiliency, risk propensity, and mindfulness should also be considered (Dubas, Baams, Doornwaard, & van Aken, 2017;Grevenstein et al, 2018;Zhang, Highhouse, & Nye, 2018). A third limitation of the study is the demographic characteristics of the sample, which consisted of mostly female undergraduate students in psychology.…”
Section: Discussionmentioning
confidence: 99%
“…Antonovsky described these as "generalized resistance resources" and sense of coherence denotes a person's ability to use them (Lindström, 2001). In the past, sense of coherence has been found to outperform other health-beneficial constructs when predicting psychological symptoms or substance use (Grevenstein, Aguilar-Raab, & Bluemke, 2019;Grevenstein, Aguilar-Raab, Schweitzer, & Bluemke, 2016;Grevenstein, Bluemke, & Kroeninger-Jungaberle, 2016).…”
Section: Sense Of Coherencementioning
confidence: 99%
“…Grevenstein et al (2017) noted the importance of investigating heterogeneity in the subscales of SOC (comprehensibility, manageability, and meaningfulness), even though Antonovsky (1993) did not recommend analyzing them in isolation. In a quantitative study, Grevenstein et al (2018) found that these three subscales have different relationships with psychological distress. Therefore, in verifying the relationship between SOC and the Big Five, it may be important to analyze the individual subscales of SOC.…”
Section: Introductionmentioning
confidence: 99%